The New Strategy to Improve Indonesia’s National Economic Growth - Abdullah , Said; Gunawan , Kazan (Journal of Ecohumanism, 2024)
Post-order new economic growth has decreased. The source of the decline in economic growth is that state revenues in the oil and gas sector have decreased. Indonesia needs more consistent high economic growth to accelerate Indonesia’s leap to become a high-income country. In this situation Thus, there are several challenges so that Indonesia can achieve growth targets and, at the same time maintain growth The challenges that must be faced​ in the form of quality sources of Power are human beings who still have valued investment in resources Power life and wealth intellectuals who are still low, plus with Posture exports that have not been worth economy high. With this, an appropriate policy strategy is needed for the three things above to become locomotives of future economic growth. Although Indonesia needs high economic growth, several boundaries must be adhered to, namely, the nature of economic growth must be inclusive, so as not to widen the gap in social inequality. A growth economy must be supported by a diversity of rich life and, at the same time intended to guard sustainability naturally as a source of main Continuity of Development and Justice between generations.